2008
DOI: 10.1080/09650790701833063
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the value of service user involvement in data analysis: ‘Our interpretation is about what lies below the surface’

Abstract: In this article the process and outcomes of service user involvement in the analysis of data are discussed. The analysis formed part of a doctoral participatory research project, which involved researcher and service users working together. The focus of the research was on the experience and needs of service users with life limiting conditions including any influence on the experience produced by social factors. Service users with a range of life limiting conditions took part in the research. A separate group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 16 publications
1
60
0
Order By: Relevance
“…clinical trials [21]); and different stages of the research process (e.g. prioritisation [22], interpretation [23]). …”
Section: The Case For Public Involvement In Health Researchmentioning
confidence: 99%
“…clinical trials [21]); and different stages of the research process (e.g. prioritisation [22], interpretation [23]). …”
Section: The Case For Public Involvement In Health Researchmentioning
confidence: 99%
“…First, Cotterell, a palliative care nurse researcher, worked with a group of service users with life-limiting conditions to understand more about the experiences and palliative care needs of others with life-limiting conditions. 22 Cotterell found that his analysis produced different results to that of the service user group, with Cotterell focussing on the professional and service users focussing on the emotional and the critical. To Cotterell, this demonstrated that service users are '"agents of knowledge" and, despite substantial difficulties, can also be willing and able to contribute to new knowledge production'.…”
Section: Hearing the Voices Of Service Users In Collaborative Analysesmentioning
confidence: 99%
“…Cotterell () describes a robust process of collaborative and iterative analysis including a “series of 10 analysis sessions in which all transcripts were analyzed in turn, four theme generation sessions, one session to expand or collapse the analysis into final themes, and, lastly, a session to integrate phase one and two themes where possible” (p. 667). Hutnik, Smith and Koch () describe an interesting process of iterative story creation, and Castleden, Garvin, and Huu‐ay‐aht () as well as Jacklin and Kinoshameg () describe training community members to work as data analysts.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, our review highlights that while research "participants" in PR projects share the characteristic of being based in places other than postsecondary institutions, their characteristics are otherwise highly variable. For example, participants can be community organizations that provide services (e.g., Bowden et al, 2006;Checkoway & Richards-Schuster, 2003), or service users themselves (e.g., Cotterell, 2008;Taggart et al, 2013). In research focused on youth/adolescent development, "participants" were sometimes youth (e.g., Levac, 2013), but commonly parents, teachers, or youth-serving organizations.…”
Section: Definitions and Descriptions Of "Partners"mentioning
confidence: 99%
See 1 more Smart Citation